(untitled) (Journal of Science and Technology, 2016)
A field experiment was carried out to determine the nitrogen fixation ability of some soybean experimental lines and to determine the amount of residual nitrogen that could be made available to a succeeding arable crop. The study was undertaken at the Crops Research Institute, Fumesua, Kumasi. The experiment was laid out in a randomized complete block design with 3 replications. Each replication consisted of 10 plots which were randomly sown to a soybean line. The seeds were sown at a spacing of 75 cm between rows and 5 cm between plants. Data collected were nodule number per plant and nodule dry weight, number of pods per plant, number of seeds per pod, total seed yield, seed, residue and total nitrogen fixed by the soybean lines. The Total Nitrogen Difference method was used in determining the amount of N2 fixed. The results showed that all the lines nodulated freely with the naturalized rhizobia in the soil. There were significant differences, however, in the nodulation abilities of the lines. Number of nodules was negatively correlated with nodule dry weight (r=- 0.45). The amount of nitrogen fixed was positively correlated with total seed yield (r= 0.65). Line GMX 92-16-2M produced the greatest number of nodules but did not fix the greatest amount of nitrogen. Line GMX 92-6-10M left the greatest amount of nitrogen (10 kg N ha-1) in its residue. The results indicate that if farmers would grow this line, an amount of 10 kg N ha-1 would be made available to subsequent arable crop following harvesting